2009
DOI: 10.1593/neo.81360
|View full text |Cite|
|
Sign up to set email alerts
|

Noninvasive Multimodality Imaging of the Tumor Microenvironment: Registered Dynamic Magnetic Resonance Imaging and Positron Emission Tomography Studies of a Preclinical Tumor Model of Tumor Hypoxia

Abstract: In vivo knowledge of the spatial distribution of viable, necrotic, and hypoxic areas can provide prognostic information about the risk of developing metastases and regional radiation sensitivity and may be used potentially for localized dose escalation in radiation treatment. In this study, multimodality in vivo magnetic resonance imaging (MRI) and positron emission tomography (PET) imaging using stereotactic fiduciary markers in the Dunning R3327-AT prostate tumor were performed, focusing on the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 34 publications
10
102
0
Order By: Relevance
“…Regarding mechanism, we speculate that focal hypoenhancement corresponds to areas of decreased vascularity and/or tumor necrosis. Consistent with this notion, animal studies have demonstrated that regions of tumor necrosis (on pathology) correlated with deceased perfusion on CMR and reduced metabolic activity on positron emission tomography 19. Studies have also indicated that tumor necrosis corresponds to chronic ischemic injury from tissue hypoxia, which would be expected to manifest as decreased contrast uptake on DE‐CMR 20, 21.…”
Section: Discussionmentioning
confidence: 80%
“…Regarding mechanism, we speculate that focal hypoenhancement corresponds to areas of decreased vascularity and/or tumor necrosis. Consistent with this notion, animal studies have demonstrated that regions of tumor necrosis (on pathology) correlated with deceased perfusion on CMR and reduced metabolic activity on positron emission tomography 19. Studies have also indicated that tumor necrosis corresponds to chronic ischemic injury from tissue hypoxia, which would be expected to manifest as decreased contrast uptake on DE‐CMR 20, 21.…”
Section: Discussionmentioning
confidence: 80%
“…Bentzen et al [195] , Rasey et al [196] , Bentzen et al [197] , Troost et al [198] Bentzen et al [125] , Gagel et al [126] , Bruehlmeier et al [199] , Lawrentschuk et al [200] , O'Donoghue et al [72] , Piert et al [166] , Sørensen et al [201] , Gagel et al [202] , Carlin et al [203] , Chang et al [204] , Mortensen et al [127] Hatano et al [205] , Huang et al [206] , Huang et al [207] , Oehler et al [208] , Cho et al [209] , Troost et al [210] , Matsumoto et al [136] , Troost et al [198] , Dubois et al [211] Dubois et al [211] , Cherk et al [212] , Riesterer et al [213] , Lehmann et al [214] , Chen et al [215] , Campanile et al [216] , Cheng et al [217] , Sato et al [218] , Norikane et al [219] Cherk et al [212] , Eschmann et al [77] , Gagel et al [82] , Koh et al [87] , Rasey et al [220] , Vera et al…”
Section: F]fmisomentioning
confidence: 99%
“…5,6) In contrast to established cell lines cultured under normal oxygen concentrations, tumors in the body grow under a specific internal environment characterized by much lower oxygen concentrations. Tissue factor (TF) is frequently over-expressed in human tumors and exhibits dual influences through its signaling and procoagulant activity.…”
mentioning
confidence: 99%